An Investigation into the Variability of Luminous Blue Variable Stars with TESS - Becca Spejcher; Noel D. Richardson; Herbert Pablo; Marina Beltran; Payton Butler; Eddie Avila (The Astronomical Journal)
Luminous blue variables (LBVs) are enigmatic, evolved, massive stars. Their variability has been observed to be episodic with large eruptions, along with variations on timescales of days to decades. We have extracted light curves of 37 LBVs from the first 4 yr of the TESS mission. These light curves provide two years of photometric time series for stars in the LMC, with several months of data for Galactic or SMC targets. We analyze the Fourier properties of the stellar light curves to determine their characteristic frequencies and red noise amplitudes, comparing them to mass-loss parameters through H α strength, and in the case of the LMC stars, B  −  V color and luminosity as estimated by their apparent g magnitudes. We confirm the absence of correlation between any of the Fourier parameters and stellar parameters, implying that there is no trend in how these stars vary as measured with these photometric data, which may point toward these stars being an extension to the supergiant α Cygni variables and not a unique class of object with regards to their short-term variations.